Efficacy of serum leucine-rich alpha-2 glycoprotein in predicting findings of Crohn’s disease small bowel lesion in capsule endoscopy - Teppei Omori; Miki Koroku; Shun Murasugi; Ayumi Ito; Maria Yonezawa; Shinichi Nakamura; Katsutoshi Tokushige (Intestinal Research)
Background/Aims Small bowel capsule endoscopy (SBCE) is an evaluation method for small bowel (SB) lesions in Crohn’s disease (CD). However, the relationship between SBCE findings and the serological biomarker leucine-rich alpha-2 glycoprotein (LRG) remains unclear. We aimed to establish appropriate cutoff values of LRG to predict the presence of SB lesions in CD through SBCE. Methods Patients with CD with SB lesions who had undergone SBCE and LRG measurements 1 month before and after the SBCE were included. The LRG values for ulcers ≥0.5 cm and other inflammatory lesions noted in SBCE were determined using the Youden Index, and the sensitivity and specificity were calculated. Additionally, the correlation between the SBCE scores (CD Activity in Capsule Endoscopy) and LRG values was evaluated. Results Forty patients without active colorectal lesions were included in the study. When the cutoff value of LRG for SB ulcers ≥ 0.5 cm was set at 14 μg/mL, the sensitivity was 92.3%, specificity was 81.5%, positive predictive value (PPV) was 70.6%, and negative predictive value (NPV) was 95.7%. In contrast, an LRG cutoff value of 12 μg/mL without inflammatory findings had a sensitivity of 91.7%, specificity of 82.1%, PPV of 68.8%, and NPV of 95.8%. CD Activity in Capsule Endoscopy correlated well with LRG values (Spearman’s rank correlation coefficient ρ = 0.681, P<0.001). Conclusions An LRG cutoff value of 14 μg/mL may be useful in predicting the presence of SB ulcers ≥ 0.5 cm, and an LRG cutoff value of 12 μg/mL may be useful in predicting the absence of SB inflammatory findings.